1989
DOI: 10.1111/j.1600-0765.1989.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lathyrogens on the mechanical strength of the periodontal ligament in the rat mandibular first molar

Abstract: Effects of lathyrogens such as aminoacetonitrile (AAN), beta-aminopropionitrile (BAPN) and cysteamine--known inhibitors of cross-linking of collagen--on the mechanical strength of the periodontal ligament of the rat mandibular first molar were examined by measuring the ultimate load required to extract the tooth from its socket in the dissected jaw. Single injections of AAN (40 approximately 100 mg/100 g body weight) or of BAPN (100 mg/100 g body weight) caused significant decreases of the mechanical strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A close correlation has also been found between the mechanical properties and the content of insoluble collagens [Vogel, 1975[Vogel, , 1978. This has been proved by the fact that lathyrogens, which interfere with the cross-linking of collagen, diminish the mechanical strength of various connective tissues such as skin [Fry et al, 1962], bones [Vogel, 1975], aorta [Fry et al,, 1962;Lykkeet al, 1960], and periodontal ligament of the rat incisor [Ohshima, 1982], In addition, it has been suggested that the pattern of cross-linking of collagen [Moriguchi & Fujimoto, 1978] and the diameter of constituent collagen fibrils [Parry, 1988;Parry et al, 1978] closely correlated with the mechanical strength of connective tissues. Changes of most mechanical parameters at high extension during maturation was explained by an increase in the cross-linking of collagen [Vogel, 1980].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A close correlation has also been found between the mechanical properties and the content of insoluble collagens [Vogel, 1975[Vogel, , 1978. This has been proved by the fact that lathyrogens, which interfere with the cross-linking of collagen, diminish the mechanical strength of various connective tissues such as skin [Fry et al, 1962], bones [Vogel, 1975], aorta [Fry et al,, 1962;Lykkeet al, 1960], and periodontal ligament of the rat incisor [Ohshima, 1982], In addition, it has been suggested that the pattern of cross-linking of collagen [Moriguchi & Fujimoto, 1978] and the diameter of constituent collagen fibrils [Parry, 1988;Parry et al, 1978] closely correlated with the mechanical strength of connective tissues. Changes of most mechanical parameters at high extension during maturation was explained by an increase in the cross-linking of collagen [Vogel, 1980].…”
Section: Discussionmentioning
confidence: 89%
“…It has been demonstrated that the ultimate load required to extract a rat incisor from its socket increased gradually with age from 4 to 24 weeks [Chiba et al, 1980]. It has also been shown that factors such as occlusion and certain types of drugs affect the ultimate load required to extract a tooth from its socket [Chiba et al, 1981a, b;Ohshima, 1982].…”
mentioning
confidence: 99%
“…A reduction in mechanical strength of PDL fibres following lathyrogen treatment of rats has been previously demonstrated (Moxham and Berkovitz 1984;Ohshima et al 1989). It is quite possible that the reduction in bone resorption parameters is caused by the inhibition of PGE2 synthesis due to the reduced tensile strength of collagen in response to B-APN treatment.…”
Section: Discussionmentioning
confidence: 92%
“…The collagen Type-I is a major constituent of the bone and the periodontal ligament (Rao et al 1979;Veis and Sabsay 1987). It is known that B-APN can cause the reduction of mechanical strength in bone and periodontal ligament via inhibition of the tensile strength of collagen (Ohshima et al 1989;Spengler et al 1977). B-APN is known to cause an impairment of the rate of eruption of the rat incisor (Berkovitz et al 1972;Michaeli et al 1975).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not necessarily mean that the periodontal ligament of the rat incisor is a stable tissue. In fact, it has been shown that the periodontal ligament responds very sensitively to various internal and external factors such as drugs [Chiba et al, 1981;Ohshima, 1982] and occlusal conditions [Komatsu, 1988]. It is plausible that dynamic changes in the quality and quantity of the ligament are continuously occurring along the long axis of tbe incisor tChiba et al, 1990] throughout the animars life in association with the eruptive movement of the tooth.…”
Section: Discussionmentioning
confidence: 99%